Interaction and dose equivalence of salbutamol and salmeterol in patients with asthma. - Smyth, E; Pavord, I; Wong, C; Wisniewski, A; Williams, J; Tattersfield, A (1993)
OBJECTIVE: To examine the pharmacological interaction of salmeterol and salbutamol and to derive an estimate of dose equivalence of salmeterol for airway and systemic effects in patients with asthma. DESIGN: Randomised double blind crossover study. SUBJECTS: 12 patients with mild asthma. INTERVENTION: Placebo or salmeterol 50, 100, 200 micrograms given on separate days followed two hours later by inhaled salbutamol in cumulative doses up to 3600 micrograms. MAIN OUTCOME MEASURES: Change in forced expiratory volume in one second (FEV1), heart rate, plasma potassium concentration, QTc interval, tremor amplitude, and creatine kinase myocardial isoenzyme concentration. RESULTS: Compared with placebo, the mean (95% confidence interval) changes in FEV1 and heart rate after salmeterol 200 micrograms were 0.61 (0.32 to 0.90) l and 7.0 (3.8 to 10.2) beats/min. Adding salbutamol caused a large increase in FEV1 after placebo (0.69 l) with progressively smaller changes after increasing doses of salmeterol (0.19 l after salmeterol 200 micrograms). Heart rate and QTc interval increased and plasma potassium concentration decreased roughly in parallel on the four study days with a suggestion of convergence at higher doses of salbutamol. Geometric mean dose equivalences for salmeterol 50 micrograms and 100 micrograms compared with salbutamol were 4.9 and 7.8 (mean 6.4) for FEV1 and ranged from 7.1 (2.9 to 17.0) to 12.6 (4.4 to 36.4) for heart rate, plasma potassium, and tremor (mean 9.5). CONCLUSIONS: The effect of adding salbutamol to salmeterol is largely additive. Weight for weight salmeterol may be up to 10 times more potent than salbutamol. Considering its longer duration of action salmeterol 50 micrograms twice daily could be equivalent to salbutamol in doses up to 500 micrograms four to six hourly.